Integrating an interprofessional educational exercise into required medical student clerkships – a quantitative analysis - Jennifer E. Schwartz; Paul Ko; Stephanie Freed; Neelum Safdar; Megan Christman; Renee Page; Deborah R. Birnbaum; Paul M. Wallach (BMC Medical Education)
Abstract Purpose Medical students are integrated into an interprofessional team to help them learn how to provide effective, patient-centered care. Indiana University School of Medicine (IUSM) introduced a unique, easy-to-implement interprofessional exercise into each clerkship to improve students’ understanding of each professional’s contribution to patient care. Methods Between 2022 and 2023, IUSM medical students interviewed a variety of healthcare professionals engaged in the care of mutual patients using a template of questions; they wrote a brief report and evaluated the experience. Students interviewed a different professional in each clerkship to broaden their exposure. Results 3088 encounters occurred, 68% at the Indianapolis campus and 32% at regional campuses. More than 82% of students agreed or strongly agreed to each of the following prompts regarding the exercise: aided their understanding of the benefits of an interprofessional team to patient care, better understood when participation of the specific healthcare professional would benefit their patient, the experience contributed to their understanding of the role of that profession within the healthcare team, their confidence in engaging other healthcare professionals on the health care team improved, and the experience aided in understanding of their own role as a member of the health care team. Conclusion This exercise was easy to implement across a multi-campus system and improved student comprehension of the interprofessional team and indications for their engagement in patient care.